From Trocchi to trainspotting : Scottish critical theory since 1960 - Gardiner, Michael, 1970- (Edinburgh University Press, 2006)
This book charts the course of Scottish Critical Theory since the 1960s. It provocatively argues that 'French' critical-theoretical ideas have developed in tandem with Scottish writing during this period. Its themes can be read as a breakdown in Scottish Enlightenment thinking after empire - precisely the process which permitted the rise of 'theory'. The book places within a wider theoretical context writers such as Muriel Spark, Edwin Morgan, Ian Hamilton Finlay, James Kelman, Alexander Trocchi, Janice Galloway, Alan Warner and Irvine Welsh, as well as more recent work by Alan Riach and Pat Kane, who can be seen to take the 'post-Enlightenment' narrative forward. In doing so, it draws on the work of the Scottish thinkers John Macmurray and R.D. Laing as well as the continental philosophers Gilles Deleuze and Paul Virilio. Key Features Engaging polemic which connects Scottish literature with critical theory and continental thinking with Scottish philosophy. Provides a needed corrective to the 'theory-fear' which has often stopped Scotland looking at its own Enlightenment. Offers the first book-length commentary on contemporary Scottish writers, as well as re-positioning more familiar writers such as Muriel Spark and James Kelman.